Rapid concerted evolution via gene conversion at the Drosophila hsp70 genes. - Bettencourt, B.R.; Feder, M.E. (Journal of Molecular Evolution, 2002)
We analyzed nucleotide variation in the hsp70 genes of Drosophila melanogaster (five genes) and D. simulans (four genes) to characterize the homogenizing and diversifying roles of gene conversion in their evolution. Gene conversion within and between the 87A7 and 87C1 gene clusters homogenize the hsp70 coding regions; in both D. melanogaster and D. simulans, same-cluster paralogues are virtually identical, and large intercluster conversion tracts diminish 87A7/87C1 divergence. Same-cluster paralogues share many polymorphisms, consistent with frequent intracluster conversion. Shared polymorphism is highly biased toward silent variation; homogenizing conversion interacts with purifying selection. In contrast to the coding regions, some hsp70 flanking regions show conversion-mediated diversification. Strong reductions of nucleotide variability and linkage disequilibria among conversion-mediated sites in hsp70Ab and hsp70Bb alleles sampled from a single natural population are consistent with a selective sweep. Comparison of the D. melanogaster and D. simulans hsp70 genes reveals whole-family fixed differences, consistent with rapid propagation of novel mutations among duplicate genes. These results suggest that the homogenizing and diversifying roles of conversion interact to drive dynamic concerted evolution of the hsp70 genes.